The influence of culture conditions strain Acinetobacter calcoaceticus K-4 on the synthesis of surfactant - Pirog, Tatiana; Karpenko, Elena; Antoniuk, Svitlana; Shevchuk, Tetiana (My University, 2009)
It has been observed that the Acinetobacter calcoaceticus K-4 strain produces surface-active substances (SAS) while growing either on hydrophilic (ethanol) or on hydrophobic substrates (hexadecane). Maximal SAS synthesis (with a conditional SAS concentration of 3.6; emulsifying activity of culture liquid dissolved in 50 times equal to 96%) was detected with growth on an ethanol-containing medium with the addition of urea, yeast autolysate and microelements, C/N ratio 60:1 and 10% inoculate, cultivated on ethanol-containing medium by the end of the exponential phase of growth. With respect to its chemical nature, extracellular SAS synthesized by A. calcoaceticus K-4 growing on ethanol-containing medium under optimal cultivating conditions form a glycolipid–aminolipid complex.
Keywords: biosurfactants; поверхностно-активные вещества; ethanol; condition cultivation; поверхнево-активні речовини; етанол; умови культивування; этанол; условия культивирования; кафедра біотехнології і мікробіології